2021
DOI: 10.1042/cs20201399
|View full text |Cite
|
Sign up to set email alerts
|

Promyelocytic leukemia protein promotes the phenotypic switch of smooth muscle cells in atherosclerotic plaques of human coronary arteries

Abstract: Promyelocytic leukemia protein (PML) is a constitutive component of PML nuclear bodies (PML-NBs), which function as stress-regulated SUMOylation factories. Since PML can also act as a regulator of the inflammatory and fibroproliferative responses characteristic of atherosclerosis, we investigated whether PML is implicated in this disease. Immunoblotting, ELISA and immunohistochemistry showed a strong up-regulation of PML in segments of human atherosclerotic coronary arteries compared to non-atherosclerotic one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…And while TSVD latent 53, the third contributing factor to peripheral vascular disease, does include GO processes related to cardiovascular morphology and function, it only predominantly prioritizes PITX2, and none of the other important genes implicated by GUIDE latent 8. For GUIDE, the third highest factor, GUIDE latent 64, significantly prioritizes genes such as AHR, PML, GDNF, and IRX1-3, which were not tagged by TSVD latent factors, but were recently implicated in important mechanisms contributing to vascular disease, such as vascular inflammatory pathways, atherosclerosis, endothelial dysfunction, and oxidative stress [34,35,36,37]. Running a GUIDE model on an LD-pruned set of FinnGen data [38] (r 2 < 0.2, with 188,140 SNPs and 2408 traits) revealed additional insights not found in the UKB models.…”
Section: Isolating Molecular Pathophysiological Pathways Of Alzheimer...mentioning
confidence: 99%
“…And while TSVD latent 53, the third contributing factor to peripheral vascular disease, does include GO processes related to cardiovascular morphology and function, it only predominantly prioritizes PITX2, and none of the other important genes implicated by GUIDE latent 8. For GUIDE, the third highest factor, GUIDE latent 64, significantly prioritizes genes such as AHR, PML, GDNF, and IRX1-3, which were not tagged by TSVD latent factors, but were recently implicated in important mechanisms contributing to vascular disease, such as vascular inflammatory pathways, atherosclerosis, endothelial dysfunction, and oxidative stress [34,35,36,37]. Running a GUIDE model on an LD-pruned set of FinnGen data [38] (r 2 < 0.2, with 188,140 SNPs and 2408 traits) revealed additional insights not found in the UKB models.…”
Section: Isolating Molecular Pathophysiological Pathways Of Alzheimer...mentioning
confidence: 99%
“…In terms of dysregulation of gene expression, cell proliferation, inflammatory response, and plaque VSMC clonality, some investigators have begun to focus their attention to proteins traditionally thought of as tumor promotors and tumor suppressor proteins as important players in atherogenesis. In this volume of Clinical Science, Karle et al [7] investigate the expression and functional ramifications of promyelocytic leukemia protein (PML) in development of atherosclerosis. Fittingly named, PML is a protein first detected in acute promyelocytic leukemia initially and classified as a tumor suppressor protein [8,9].…”
Section: Promyelocytic Leukemia Proteinmentioning
confidence: 99%
“…Previous studies have shown that numerous genes contribute to plaque stabilization by regulating SMC phenotypic switching [20][21][22][23] . Two challenges have been identified.…”
Section: Introductionmentioning
confidence: 99%